Electronic engineering and information science proceedings of the 2015 International Conference on Electronic Engineering and Information Science (ICEEIS 2015), 17-18 January, 2015, Haikou, P.R. China - Wang, Dongxing (CRC Press/Balkema, 2015)
The International Conference of Electronic Engineering and Information Science 2015 (ICEEIS 2015) was held on January 17-18, 2015, Harbin, China. This proceedings volume assembles papers from various researchers, engineers and educators engaged in the fields of electronic engineering and information science. The papers in this proceedings volume consist of topics such as: Electronic Engineering, Information Science and Information Technologies, Computational Mathematics and Data Mining, Image Processing and Computer Vision, Communication and Signal Processing, Control and Automation of Mechatronics, Methods, Devices and Systems for Measurement and Monitoring, Engineering of Weapon Systems, Mechanical Engineering and Material Science and Technologies of Processing